Applied econometrics - Asteriou, Dimitrios; Hall, Stephen G. (New Delhi Bloomsbury, 2022)
This book will be essential reading for economics undergraduate and master's students taking a course in applied econometrics. Its practical nature makes it ideal for modules requiring a research project. New to this Edition: - Additional practical exercises throughout to help consolidate understanding - A freshly-updated companion website featuring a new solutions manual for instructors.
Keywords: Dynamic Econometrics; Modern Econometrics